2014
DOI: 10.1108/ijmce-12-2012-0078
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship in a Japanese graduate school: learning through apprenticeship

Abstract: Purpose – The purpose of this study is to investigate a four-year mentorship program for Japanese graduate students at a private university in Tokyo, Japan. The following research questions were investigated: First, does mentorship provide effective and adequate preparation needed for graduate students to perform competitively (e.g. attending conferences, publishing in journals, etc.) in academic forums? Second, what kinds of benefits are gained by the mentees? Third, what factors are conducive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…More research studies were conducted to investigate the impact of mentorship programs on teachers' professional development. (Cosgun & Atay, 2018;Sakamoto & Lumi, 2014). Cosgun and Atay (2018) explored the impact of a mentoring program provided to EFL teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More research studies were conducted to investigate the impact of mentorship programs on teachers' professional development. (Cosgun & Atay, 2018;Sakamoto & Lumi, 2014). Cosgun and Atay (2018) explored the impact of a mentoring program provided to EFL teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings showed that the program contributed to the teachers' professional and personal development. Sakamoto and Lumi (2014) investigated the impact of a mentorship program on graduate students. The findings showed that mentoring which encouraged active participation in professional activities could foster mentees' confidence and provides training for them to perform well in forums.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Japan, for instance, the tradition of respect and authority has implications in the development of the relationship between mentor and mentee (Sakamoto and Tamanyu, 2014). On the other hand, there is also a strong culture of equality in schools and a novice teacher faces the added challenge of being regarded as an equal by other teachers and, therefore, "there is no need to teach a novice what to do (all they need to do is to observe and emulate what they see more experienced teachers doing)" (Asada, 2012, p. 59).…”
Section: Context and Cultural Influences On Mentoringmentioning
confidence: 99%
“…Although it is hard to define, the authors of the papers reviewed suggest that mentoring is traditionally seen as a process by which a more experienced person (the mentor) gives support to a less experienced person (the mentee) across a wide range of issues relevant to work and professional development (D'Souza, 2014;Garza et al, 2014;Godden et al, 2014;Hobson and Malderez, 2013;Kutsyuruba, 2012;Sakamoto and Tamanyu, 2014;Stephens et al, 2014;Wyatt and Arnold, 2012). Whilst some definitions of mentoring do not explicitly refer to the mentee as having less experience than the mentor, the general notion of mentoring as a "developmental partnering of two professionals, in which one individual is sharing his or her knowledge and expertise to inform or support the professional learning and career development of another" (Parylo et al, 2012, p. 121) is evident in the majority of the 37 papers reviewed.…”
Section: Ijmce 54mentioning
confidence: 99%
See 1 more Smart Citation